Photorheological Ionic Liquids - Avo, Joao; Cidade, M.T.; Rodriguez, Vincent; Lima, Joao C.; Jorge Parola, A. (Journal of Physical Chemistry B, 2015)
n/a
Lima, Joao Carlos/K-2890-2014; Lima, Joao/F-3658-2010; Avo, Joao/C-6939-2013; Rodriguez, Vincent/B-9163-2008; Cidade, Maria Teresa/H-7462-2013 Lima, Joao/0000-0003-0528-1967; Avo, Joao/0000-0002-3380-748X; Rodriguez, Vincent/0000-0001-6804-9757; Cidade, Maria Teresa/0000-0001-8261-6754 0